Integrating albedo offsets in reforestation decisions for climate change mitigation outcomes in 2050: A case study in the USA - Lucas K. Johnson; Zhiqiang Yang; Angela Erb; Ryan M. Bright; Grant M. Domke; Tracey S. Frescino; Crystal B. Schaaf; Sean P. Healey (Forest Ecology and Management, 2025)

Congruent Long‐Term Declines in Carbon and Biodiversity Are a Signature of Forest Degradation - Matthew G. Betts; Zhiqiang Yang; John S. Gunn; Sean P. Healey (Global Change Biology, 2024)
Recent global policy initiatives aimed at reducing forest degradation require practical definitions of degradation that are readily monitored. However, consistent approaches for monitoring forest degradation over the long term and at broad scales are lacking. We quantified the long‐term effects of intensive wood harvest on above‐ground carbon and biodiversity at fine resolutions (30 m 2 ) and broad scales (New Brunswick, Canada; 72,908 km 2 ). Model predictions for above‐ground biomass were highly correlated with independent data ( r = 0.77). After accounting for carbon stored in wood products, net CO 2 emissions from forests for the region from 1985 to 2020 were 141 CO 2 e Tg (4.02 TgCO 2 e year −1 ; 32% of all reported emissions). We found strong positive correlations between locations with declines in above‐ground carbon and habitats for old‐forest bird species, which have lost > 20% habitat over 35 years. High congruence between biodiversity and forest carbon offers potential for policy incentives to conserve both objectives simultaneously and slow rates of forest degradation. These methods could be used to track forest degradation for managed forest regions worldwide.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Coupling non‐invasive physiological assessments with telemetry to understand inter‐individual variation in behaviour and survivorship of sockeye salmon: development and validation of a technique - S. J. Cooke; G. T. Crossin; D. A. Patterson; K. K. English; S. G. Hinch; J. L. Young; R. F. Alexander; M. C. Healey; G. Van Der Kraak; A. P. Farrell (Journal of Fish Biology, 2005)
Approximately 200 km from the mouth of the Fraser River, British Columbia, Canada, adult sockeye salmon Oncorhynchus nerka , were gastrically implanted with radio transmitters without anaesthetic. Subsets of the transmitter implanted fish were also biopsied which included drawing blood from the caudal peduncle (3 ml), removal of gill tissue (0·03 g) and quantification of energetic status using a microwave fat meter. Several experiments were used to test the hypothesis that the biopsy had a negligible effect on the subsequent survival and migratory behaviour of transmitter implanted fish. In the first experiment, no difference was found in the survival (both 100%) or tag retention (both 100%) between the two treatment groups (transmitter implanted with and without biopsy) when fish were held in pens for 24 h in the marine environment. Similarly, in other experiments where fish were released to the ocean to resume their migratory journey, no statistical differences were found in the travel times of fish in the two treatment groups, or in the proportion of fish that passed in‐river telemetry checkpoints. These results indicated that the handling and biopsy methods produced similar levels of mortality and tag retention as the telemetry treatment alone and that any changes in behaviour between the two treatment groups did not adversely affect migration time. Based upon the evidence provided from the biotelemetry of >300 adult sockeye salmon, it was felt that this general type of approach could be applicable to other fish species.

Energetics and morphology of sockeye salmon: effects of upriver migratory distance and elevation - G. T. Crossin; S. G. Hinch; A. P. Farrell; D. A. Higgs; A. G. Lotto; J. D. Oakes; M. C. Healey (Journal of Fish Biology, 2004)
Depending on population, wild Fraser River sockeye salmon Oncorhynchus nerka travel distances of 1100 km and ascend elevations ranging from near sea‐level to 1200 m to reach spawning areas. Populations embarking on distant, high elevation migrations ( i.e . Early Stuart, Chilko and Horsefly populations) began their upriver spawning migrations with higher densities of somatic energy ( c . 9·2 to 9·8 MJ kg −1 ) and fewer eggs ( c . 3200 to 3800) than populations making shorter, low elevation migrations ( i.e . Weaver and Adams; c . 7·1 to 8·3 MJ kg −1 gross somatic energy and c . 4300 to 4700 eggs). Populations making difficult upriver migrations also had morphologies that were smaller and more fusiform than populations making less difficult migrations, traits that may facilitate somatic energy conservation by reducing transport costs. Indeed, fish travelling long distances expended less somatic energy per unit of migratory difficulty than those travelling shorter distances (2·8 to 3·8 kJ v . 10–1400 kJ). Consistent with evolutionary theory, difficult migrations appear to select for energy efficiency but ultimately fish making more difficult migrations produce fewer eggs, even when differences in body length have been accounted for. Despite large among‐population differences in somatic energy at the start of upriver migration, all populations completed migration and spawning, and subsequently died, with c . 4 MJ kg −1 of energy remaining, a level which may reflect a threshold to sustain life.

The effect of exercise and captivity on energy partitioning, reproductive maturation and fertilization success in adult sockeye salmon - D. A. Patterson; J. S. Macdonald; S. G. Hinch; M. C. Healey; A. P. Farrell (Journal of Fish Biology, 2004)
Releasing a population of adult Fraser River sockeye salmon Oncorhynchus nerka from an energetically more expensive non‐feeding natural migration (1089 km, natal groups) and allowing them to sexually mature in either a moderate flow (captive exercise group) or a no flow (captive non‐exercise group) environment resulted in significant differences in body energy densities (MJ kg −1 ) among groups (ranked: initial natural migrator > non‐exercise > exercise > natal arrivals). Similarly, per cent body lipids were significantly lower in exercise females compared with non‐exercise females, experimentally confirming the central role lipid catabolism has in powering swimming. Although restricting exercise did result in greater body energy reserves at spawning, this did not result in a reallocation of energy to reproduction, as fecundity, egg size and gonad composition were unchanged among the groups. Furthermore, non‐exercise females had delayed maturity, lower egg deposition rates, and were more likely to die prior to egg ovulation than exercise females and natal spawners. Eggs from captive exercise adult females were more likely to survive to the eyed stage than eggs from captive non‐exercise females, but both captive groups had significantly lower egg fertilization success than natal spawners suggesting that confinement stress played a role in some of results presented. There were no significant differences in plasma levels of glucose, lactate, cortisol and reproductive hormones among the groups, but correlations among acute and chronic indicators of stress were significant among individuals. These results indicate that exercise during the late stages of maturation, as might occur normally, may be required for optimizing reproductive maturation and maximizing reproductive success.

Field‐based measurements of oxygen uptake and swimming performance with adult Pacific salmon using a mobile respirometer swim tunnel - A. P. Farrell; C. G. Lee; K. Tierney; A. Hodaly; S. Clutterham; M. Healey; S. Hinch; A. Lotto (Journal of Fish Biology, 2003)
Novel field measurements of critical swimming speed ( U crit ) and oxygen uptake ( M o 2 ) in three species of adult Pacific salmon Oncorhynchus spp. up to 3·5 kg in body mass were made using two newly designed, mobile Brett‐type swim tunnel respirometers sited at a number of field locations in British Columbia, Canada. Measurements of U crit , which ranged from 1· 68 to 2·17 body lengths s −1 , and maximum M o 2 , which ranged from 8·74 to 12·63 mg O 2 kg −1 min −1 depending on the species and field location, were judged to be of similar quality when compared with available data for laboratory‐based studies. Therefore high quality respirometry studies were possible in the field using adult wild swimming salmonids. In addition, the recovery of wild adult Pacific salmon from the exhaustive U crit swim test was sufficiently rapid that swimming performance could be repeated with M o 2 being reestablished. This result suggests that wild adult salmon are capable of carrying a moderate excess post‐exercise oxygen consumption without adversely affecting U crit , maximum M o 2 or swimming economy. Such capabilities may be extremely important for timely migratory passages when salmonids face repetitive hydraulic challenges on their upstream migration.

A methodological appraisal of the impact of different classification procedures used in three different phases of the australian rheumatoid arthritis twin survey - N. Bellamy; D. L. Duffy; P. Sambrook; R. R. C. Buchanan; P. M. Brooks; H. Dunckley; S. C. Healey; S. Mason; N. G. Martin (Inflammopharmacology, 1998)